PERAN ONLINE CUSTOMER REVIEW DAN MINAT BELI SEBAGAI MEDIASI DALAM PENGAMBILAN KEPUTUSAN BELANJA PRODUK KOSMETIK PADA PLATFORM E-COMMERCE - Sutopo Sutopo; Sudianto; Abdul Hamid (Universitas Muhammadiyah Jakarta, 2026)
This study investigates the role of online customer reviews (OCR) and purchase intention as mediating variables in the decision-making process for purchasing cosmetic products on e-commerce platforms. The rapid growth of digital commerce in Indonesia has transformed consumer behavior, making OCR a critical touchpoint in purchase journeys. Using a quantitative approach, data were collected from 250 respondents via purposive sampling among active e-commerce users aged 18–35 who had purchased cosmetics online within the last six months. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results indicate that OCR positively and significantly influences purchase intention (β=0.512, p<0.01) and purchase decision (β=0.348, p<0.01). Purchase intention fully mediates the relationship between OCR and purchase decision (indirect effect β=0.261, p<0.01). These findings confirm that credibility and valence of OCR substantially shape consumer trust and buying behavior in the cosmetic e-commerce context. Managerial implications suggest that cosmetic brands must strategically manage review ecosystems to convert digital engagement into purchase decisions.